A graphite phase carbon nitride-based titanium dioxide doped lithium aluminum hydride hydrogen storage material and its preparation method and application
Through the ball milling of graphite phase carbon nitride and titanium dioxide composite material and lithium aluminum hydride, the TiO2@g-C3N4 catalyst is formed, which solves the problems of poor reversibility and slow desorption kinetics of lithium aluminum hydride, and achieves efficient hydrogen storage performance and The simplified preparation process reduces production costs and operational difficulties.
Patent Information
- Application Number
- CN202310756099.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-26
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2043-06-26
AI Technical Summary
Among existing hydrogen storage materials, the poor reversibility of lithium aluminum hydride and slow desorption kinetics are problems, especially the poor dehydrogenation performance caused by the agglomeration of TiO2 nanoparticles. Common carriers such as tetrahydrofuran are toxic solvents, and the preparation process is complicated and cannot be met. Application requirements.
Using a composite material of graphite phase carbon nitride and titanium dioxide, control moisture through infrared light, avoid side reactions, simplify the preparation process, prepare TiO2@g-C3N4 catalyst, and ball mill with lithium aluminum hydride to form graphite phase carbon nitride-based titanium dioxide Doped lithium hydride hydrogen storage material.
The initial hydrogen release temperature is significantly reduced and the amount of hydrogen release is increased, the kinetic performance of hydrogen storage materials is improved, the preparation process is simplified, the production cost and operation difficulty is reduced, and the agglomeration phenomenon is avoided.
Smart Images

Figure CN116768151B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of hydrogen storage materials, and in particular to a graphite phase carbon nitride-based titanium dioxide doped lithium aluminum hydride hydrogen storage material and a preparation method and application thereof. Background Art
[0002] Among hydrogen storage materials, lithium aluminum hydride has the advantages of abundant content, environmental friendliness, and mild operating temperature and pressure. However, lithium aluminum hydride has the problems of poor reversibility and slow desorption kinetics. Common solutions are nanocatalyst doping, nanoconfinement, and composite with other hydrogen storage materials.
[0003] Among them, the problem of slow desorption kinetics can be solved by doping transition metal compounds. Among transition metal compounds, TiO2 is a common doping material used to improve the dehydrogenation performance of LiAlH4. For example, in existing document 1 (PBAmama, JTGrant, PJShamberger, et al. Improved Dehydrogenation Properties of Ti-Doped LiAlH4: Role of Ti Precursors, Journal of Physical Chemistry C 116 (2012) 21886-21894.), LiAlH4 is ball-milled and doped with commercially purchased TiO2 nanoparticles, and the initial dehydrogenation temperature is reduced from 148°C to 116°C. The problem with this technical solution is that the dehydrogenation temperature is still very high and cannot meet the application requirements. The main reason for this technical problem is that according to the relevant records about SEM in existing document 1, the TiO2 nanoparticles obtained by this technical solution agglomerate, resulting in poor dehydrogenation performance.
[0004] In order to solve the above-mentioned agglomeration problem, it can be improved by adding a carrier. For example, in the existing document 2 (Zhao Y, Han M, Wang H. LiAlH4 supported on TiO2 / hierarchically porous carbonnanocomposites with enhanced hydrogen storage properties [J]. InorganicChemistry Frontiers, 2016.), a TiO2 / HPC nanocomposite material with HPC derived from a carbon source as a carrier was prepared by self-assembly using a silica source and a carbon source as raw materials. Then, LiAlH4 was dissolved in tetrahydrofuran distillate, and TiO2 / HPC was dispersed in the tetrahydrofuran solution. Finally, the two were stirred and mixed, and then tetrahydrofuran was evaporated to achieve the doping of TiO2 and C with LiAlH4. The technical effect of reducing the starting hydrogen desorption temperature from 148°C to 64°C was obtained. There are two technical problems in this technical solution: 1. Tetrahydrofuran is a toxic solvent, and the preparation process needs to be evaporated, which directly leads to the need for a precise reaction container to provide sealing and heating conditions in the preparation process; 2. The content of LiAlH4 in the final composite material is only 37%, resulting in a hydrogen release of 4.3wt% at 130°C, which is far from meeting the application requirements.
[0005] At the same time, according to the existing literature 3 (Ismail M, Zhao Y, Yu XB, et al. Improved hydrogen storage property of LiAlH4 by milling with carbon based additives [J]. Electroactive materials society, 2013.), it can be seen that carbon materials as carriers, including carbon black, nano-carbon powder, graphite and single-walled nanotubes, have significant differences in technical effects when doped with LiAlH4.
[0006] Based on the above existing literature, it can be known that by adjusting TiO2 and the carrier to achieve a synergistic effect between the two, the performance of the composite material can be effectively improved. Therefore, in the previous work of the research group of the present invention, the existing document 4 (patent application number 202310194658X A hollow flower-shaped M-NC@TiO2 composite material and its preparation method and application), first, prepare solid spherical TiO2, and then prepare it into hollow spherical TiO2; then, orderly grow M-MOF on the surface of hollow spherical TiO2 to obtain M-MOF@TiO2; finally, calcination is performed to obtain M-NC@TiO2 composite material. The basic principle of this technical solution is to achieve uniform doping of nanoparticles and avoid agglomeration by adjusting the microscopic morphology of TiO2 and preparing M-MOFs and then calcining. And finally, the technical effect of the initial hydrogen release temperature of 56.3°C and the hydrogen release amount of 7.3wt% is obtained. However, this technical solution still has the following technical problems: the preparation method has complicated steps and requires two hydrothermal treatments and one calcination treatment, which significantly affects the production cost and quality consistency in actual production.
[0007] Therefore, the actual technical problem that the existing technology needs to solve is to prepare a catalyst material with high catalytic activity through a simple process under the premise of ensuring the initial hydrogen desorption temperature and hydrogen desorption amount. Summary of the invention
[0008] The purpose of the present invention is to provide a graphite phase carbon nitride-based titanium dioxide doped lithium aluminum hydride hydrogen storage material and a preparation method thereof. The basic principle is that the composite material of graphite phase carbon nitride and titanium dioxide can be doped to make Li + The charge of [AlH4] is shifted. In order to ensure charge balance, - The charge of the group also changes, causing the Al-H bond to break, accelerating the decomposition of the product during the reaction, accelerating the progress of the entire reaction, and promoting the generation of H2, thereby improving the hydrogen release performance of LiAlH4; in terms of technical processes, during the pretreatment process, infrared light is used to control moisture and effectively avoid the occurrence of side reactions. By replacing the conventional operation that requires argon conditions, that is, the operation performed in a glove box, the difficulty of operation and the requirements for instruments are significantly reduced.
[0009] In order to achieve the above-mentioned invention object, the specific technical solution adopted by the present invention is:
[0010] A graphite-phase carbon nitride-based titanium dioxide doped with lithium aluminum hydride hydrogen storage material, using dicyandiamide and titanyl sulfate as raw materials, dicyandiamide as a carbon source and a nitrogen source, and titanyl sulfate as a titanium source; after grinding and mixing, calcining is performed to obtain TiO2@g-C3N4, and then ball milling is performed with lithium aluminum hydride to obtain a graphite-phase carbon nitride-based titanium dioxide doped with lithium aluminum hydride hydrogen storage material;
[0011] The doping amount of the TiO2@g-C3N4 is 3-10wt%;
[0012] The microstructure of the g-C3N4 is a porous structure, the microstructure of TiO2 is a nanoparticle structure, the particle size of the TiO2 nanoparticles is 8-9nm, and the microstructure of TiO2@g-C3N4 is that TiO2 is uniformly loaded on the surface of g-C3N4.
[0013] A method for preparing a graphite phase carbon nitride-based titanium dioxide doped lithium aluminum hydride hydrogen storage material comprises the following steps:
[0014] Step 1, pretreatment of raw materials, grinding dicyandiamide and titanyl sulfate under certain conditions and in a certain mass ratio to obtain a mixture TC-F;
[0015] In the step 1, the grinding condition is infrared irradiation, and the grinding time is 0.5-1h; the mass ratio of dicyandiamide to titanyl sulfate is (1-3):1;
[0016] Step 2, preparation of graphite phase carbon nitride-based titanium dioxide, calcining the TC-F obtained in step 1 under certain conditions; finally, grinding the calcined product under certain conditions, and drying under certain conditions to obtain graphite phase carbon nitride-based titanium dioxide, named TiO2@g-C3N4;
[0017] In step 2, the calcination conditions are: in air, the heating rate is 3-10°C / min, the calcination temperature is 440-550°C, and the calcination time is 2-4h; the grinding time is 0.5-1h; the drying conditions are: the drying temperature is 60-80°C, and the drying time is 6-12h;
[0018] Step 3, preparation of graphite phase carbon nitride-based titanium dioxide doped with lithium aluminum hydride hydrogen storage material, using the TiO2@g-C3N4 obtained in step 1 as a catalyst, with a certain doping amount, TiO2@g-C3N4 and LiAlH4 are ball-milled under certain conditions to obtain a graphite phase carbon nitride-based titanium dioxide doped with lithium aluminum hydride hydrogen storage material, named LiAlH4 / TiO2@g-C3N4;
[0019] In the step 3, the doping amount of TiO2@g-C3N4 is 3-10wt%; the ball milling conditions are: under argon conditions, the ball-to-material ratio is (100-200):1, the ball milling speed is 250-500rpm, and the ball milling time is 0.5-1h.
[0020] A graphite phase carbon nitride-based titanium dioxide doped lithium aluminum hydride hydrogen storage material is used as a hydrogen storage material, with an initial hydrogen release temperature of 72-82.3° C., a hydrogen release amount of 6.6-7.3wt%, and a hydrogen release rate of 69.8-71.7%.
[0021] The test results of the material obtained by the present invention are as follows:
[0022] XRD test shows that TC-F contains characteristic peaks of titanyl sulfate and dicyandiamide; TiO2@g-C3N4 contains characteristic peaks of TiO2 and g-C3N4; this proves that the present invention successfully prepares TiO2@g-C3N4 by a one-step calcination method. TC contains not only characteristic peaks of titanyl sulfate and dicyandiamide, but also characteristic peaks of TiH(SO4)2 4H2O, which proves that dicyandiamide and titanyl sulfate react during grinding without infrared irradiation, that is, infrared irradiation can inhibit the decomposition reaction of titanyl sulfate.
[0023] Through SEM test and TEM test, it can be known that in the TiO2@g-C3N4 prepared by the present invention, g-C3N4 has a porous structure, TiO2 has a nanoparticle structure with a particle size of 8-9nm, and TiO2 is uniformly loaded on the surface of g-C3N4.
[0024] Through programmed temperature-rising hydrogen decomposition experimental tests, it was found that the initial hydrogen decomposition temperature of LiAlH4 / TiO2@g-C3N4-7 dropped to 76°C, the hydrogen decomposition amount reached 6.9wt%, and the hydrogen decomposition rate was 70.6%; the doping of TiO2@g-C3N4 reduced the hydrogen decomposition temperature of the LiAlH4 system, and its hydrogen decomposition performance was greatly improved.
[0025] The hydrogen decomposition kinetics test showed that at 90°C, LiAlH4 / TiO2@g-C3N4-7 released 3.5wt% hydrogen in 60 minutes, with a decomposition rate of 35.8%; at 200°C, LiAlH4 / TiO2@g-C3N4-7 released 6.7wt% hydrogen in 20 minutes, with a decomposition rate of 68.6%.
[0026] Therefore, the present invention has the following advantages over the prior art:
[0027] 1. The TiO2 nanoparticles prepared by the present invention are dispersed on a graphite phase g-C3N4 carrier to construct an effective composite catalyst for LiAlH4, which can effectively improve the hydrogen storage performance of the hydrogen storage material;
[0028] 2. The present invention effectively controls moisture through the effect of infrared light, inhibits the decomposition of titanyl sulfate, increases the purity of the hydrogen storage catalyst, and improves the catalytic performance of the hydrogen storage catalyst; compared with the prior art, the preparation process of infrared light is significantly reduced by conducting experiments in a glove box under argon conditions, which is specifically reflected in the difficulty of operation and the requirements for instruments;
[0029] 3. The hydrogen storage material prepared by the present invention has good hydrogen storage kinetics. At 120°C, 4.9wt% hydrogen is released in 50 minutes, and at 200°C, 6.7wt% hydrogen is released in 20 minutes;
[0030] 4. The present invention effectively controls the consistency of the final product, which is achieved specifically in two aspects: first, a one-step calcination method is adopted to reduce the operation steps and reduce the error accumulation; second, commercially purchased titanyl sulfate and dicyandiamide are used as raw materials to ensure the consistency of the raw materials; the improvement of consistency and the low cost of raw materials ultimately reduce the production cost;
[0031] 5. The present invention improves the purity of the catalyst through a one-step calcination method while preventing the agglomeration of the hydrogen storage material, thereby achieving the technical effects of lowering the dehydrogenation temperature of LiAlH4 and increasing the dehydrogenation amount. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 XRD spectra of TiO2-E, TIOS, g-C3N4 and TiO2@g-C3N4 obtained in Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 6 of the present invention;
[0033] Figure 2 XRD patterns of TC-F and TC obtained in Example 1 and Comparative Example 1 of the present invention;
[0034] Figure 3 TEM image of TiO2@g-C3N4 prepared in Example 1 of the present invention;
[0035] Figure 4 This is a SEM image of TiO2@g-C3N4 prepared in Example 1 of the present invention;
[0036] Figure 5 The temperature increase hydrogen release curves of LiAlH4 without any catalyst and doped with TiO2@g-C3N4 with the doping amount of 3wt%, 7wt% and 10wt% respectively in Example 1, Example 2, Example 3 and Comparative Example 4 of the present invention;
[0037] Figure 6The kinetic hydrogen release curves of LiAlH4-90, LiAlH4 / TiO2@g-C3N4-7-90 and LiAlH4 / TiO2@g-C3N4-7-90-200 hydrogen storage materials in Example 1 and Comparative Example 4 of the present invention;
[0038] Figure 7 It is a temperature increase hydrogen release curve diagram of LiAlH4-TC, LiAlH4-g-C3N4, LiAlH4-TiOS, LiAlH4-TiO2-E and LiAlH4 / TiO2@g-C3N4-7 series hydrogen storage materials in Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 6 of the present invention;
[0039] Figure 8 It is a temperature-increasing hydrogen release curve of LiAlH4-TiO2-Eg-C3N4 and LiAlH4-TiO2-Eg-CNTs series hydrogen storage materials in Comparative Examples 6 and 7 of the present invention. DETAILED DESCRIPTION
[0040] The present invention is further described in detail through embodiments and in conjunction with the accompanying drawings, but the present invention is not limited thereto.
[0041] Example 1
[0042] A method for preparing a graphite phase carbon nitride-based titanium dioxide doped lithium aluminum hydride hydrogen storage material comprises the following steps:
[0043] Step 1, pretreatment of raw materials, grinding 5g of dicyandiamide and 5g of titanyl sulfate under infrared irradiation for 30min to obtain a mixture TC-F;
[0044] Step 2, preparation of graphite phase carbon nitride-based titanium dioxide, calcining the TC-F obtained in step 1 under air conditions at a heating rate of 5°C / min, a calcination temperature of 520°C, and a calcination time of 4h; finally, grinding the calcined product under the condition of a grinding time of 30min, and drying under the condition of a drying temperature of 60°C and a drying time of 12h to obtain graphite phase carbon nitride-based titanium dioxide, named TiO2@g-C3N4;
[0045] Step 3, preparation of graphite phase carbon nitride-based titanium dioxide doped lithium aluminum hydride hydrogen storage material, using the TiO2@g-C3N4 obtained in step 2 as a catalyst, with a doping amount of 7wt%, 0.021g TiO2@g-C3N4 and 0.279g LiAlH4 are ball milled under argon conditions with a ball-to-material ratio of 200:1, a ball milling speed of 250rpm, and a ball milling time of 30min to obtain a graphite phase carbon nitride-based titanium dioxide doped lithium aluminum hydride hydrogen storage material with a doping amount of 7wt%, named LiAlH4 / TiO2@g-C3N4-7.
[0046] In order to prove the composition of TiO2@g-C3N4 obtained in step 2, XRD test was performed on TiO2@g-C3N4. At the same time, in order to prove the effect of calcination, XRD test was performed on TC-F obtained in step 1.
[0047] The XRD test results of TiO2@g-C3N4 are as follows Figure 1 As shown, TiO2@g-C3N4 contains the characteristic peaks of TiO2 and g-C3N4;
[0048] The XRD test results of TC-F are as follows: Figure 2 As shown, TC-F contains characteristic peaks of titanyl sulfate and dicyandiamide;
[0049] The test results show that during the calcination process, dicyandiamide decomposes into g-C3N4, and at the same time, titanyl sulfate decomposes into TiO2 under the action of dicyandiamide.
[0050] In order to verify the microstructure of TiO2@g-C3N4 obtained in step 1, SEM test was performed on TiO2@g-C3N4. The test results are shown in Figure 3 As shown, g-C3N4 has a porous structure, TiO2 has a nanoparticle structure, and the overall microstructure of TiO2@g-C3N4 is that TiO2 is uniformly loaded on the surface of g-C3N4.
[0051] In order to further prove the microstructure of TiO2@g-C3N4, TEM test was carried out. The test results are shown in Figure 4 As shown, the particle size of TiO2 nanoparticles is 8-9nm.
[0052] In order to prove the hydrogen desorption kinetics of LiAlH4 / TiO2@g-C3N4-7, a temperature-programmed hydrogen desorption test was carried out. The specific method of the temperature-programmed hydrogen desorption test is to heat the sample to be tested from 25℃ to 300℃ at a heating rate of 3℃ / min. The test results are shown in Figure 2. Figure 5 As shown, the initial dehydrogenation temperature of LiAlH4 / TiO2@g-C3N4-7 is 76°C, the dehydrogenation amount is 6.9wt%, and the dehydrogenation rate is 70.6%.
[0053] In order to further demonstrate the hydrogen desorption kinetics of LiAlH4 / TiO2@g-C3N4-7, isothermal hydrogen desorption experiments were carried out at different temperatures. Figure 6 As shown,
[0054] At 90 °C, LiAlH4 / TiO2@g-C3N4-7, named LiAlH4 / TiO2@g-C3N4-7-90, released 3.5 wt% hydrogen at 60 min, with a hydrogen release rate of 35.8%;
[0055] At 200 °C, LiAlH4 / TiO2@g-C3N4-7, named LiAlH4 / TiO2@g-C3N4-7-200, released 6.7 wt% of hydrogen at 20 min, with a hydrogen release rate of 68.6%.
[0056] The test results show that LiAlH4 / TiO2@g-C3N4-7 has good hydrogen desorption kinetics.
[0057] In order to demonstrate the influence of infrared irradiation conditions, comparative example 1 is provided, which includes a mixture TC obtained without infrared irradiation conditions and a final TC-doped lithium aluminum hydride hydrogen storage material.
[0058] Comparative Example 1
[0059] A method for preparing a mixture TC under conditions without infrared irradiation, wherein the steps not specifically described are the same as those in Example 1, except that: the conditions for grinding dicyandiamide and titanyl sulfate in step 1 are that the grinding is carried out under conditions without infrared irradiation, and the resulting mixture is named a mixture of dicyandiamide and titanyl sulfate, abbreviated as TC, and finally step 3 can obtain a mixture of dicyandiamide and titanyl sulfate doped with 7wt% of TC as a lithium aluminum hydride hydrogen storage material, named LiAlH4-TC.
[0060] The XRD test results of TC are as follows: Figure 2 As shown, TC contains not only the characteristic peaks of titanyl sulfate and dicyandiamide, but also the characteristic peaks of TiH(SO4)2 4H2O. Compared with the test results of TC-F in Example 1, it can be seen that in the absence of infrared irradiation, dicyandiamide and titanyl sulfate will react during the grinding process, that is, infrared irradiation conditions can inhibit the decomposition reaction of titanyl sulfate.
[0061] By comparing Example 1 with Example 1, it can be seen that the infrared irradiation conditions have a substantial impact on grinding. The reason is that simple infrared irradiation can effectively control moisture and inhibit the decomposition of titanyl sulfate.
[0062] The test results of LiAlH4-TC's programmed temperature dehydrogenation experiment are as follows Figure 7As shown, the initial dehydrogenation temperature is 83°C, the dehydrogenation amount is 6.8wt%, and the dehydrogenation rate is 69.6%. Compared with the test results of Example 1, it can be seen that infrared irradiation can slightly increase the dehydrogenation amount, but can effectively reduce the initial dehydrogenation temperature from 83°C to 76°C.
[0063] In order to prove the role of the raw materials dicyandiamide and titanyl sulfate in the technical solution, Comparative Examples 2 and 3 are provided, which are lithium aluminum hydride-based hydrogen storage materials prepared by doping dicyandiamide and titanyl sulfate separately; at the same time, Comparative Example 4 is provided, which is LiAlH4 after ball milling of lithium aluminum hydride without any catalyst as a reference example.
[0064] Comparative Example 2
[0065] A method for preparing a lithium aluminum hydride-based hydrogen storage material doped with dicyandiamide alone, wherein the steps not specifically described are the same as those in Example 1, except that: in step 1, only dicyandiamide is doped without titanyl sulfate, the material obtained in step 2 is named g-C3N4, and finally in step 3, a graphite phase carbon nitride-doped lithium aluminum hydride hydrogen storage material with a doping amount of 7wt% is obtained, which is named LiAlH4-g-C3N4.
[0066] The XRD test results of g-C3N4 are as follows Figure 1 As shown, g-C3N4 contains the characteristic peaks of g-C3N4, but not the characteristic peaks of TiO2. The test results show that dicyandiamide, as a carbon source and nitrogen source, generates g-C3N4 during the calcination process.
[0067] The results of the programmed temperature dehydrogenation experiment of LiAlH4-g-C3N4 are as follows Figure 7 As shown, the initial dehydrogenation temperature is 119°C, the dehydrogenation amount is 6.7wt%, and the dehydrogenation rate is 68.6%. Compared with the test results of Example 1, it can be seen that the addition of dicyandiamide and titanyl sulfate can slightly increase the dehydrogenation amount, but the initial dehydrogenation temperature is significantly reduced from 119°C to 76°C, which proves that titanyl sulfate can significantly improve the dehydrogenation performance of LiAlH4.
[0068] Comparative Example 3
[0069] A method for preparing a lithium aluminum hydride-based hydrogen storage material doped with titanyl sulfate alone, wherein the steps not specifically described are the same as those in Example 1, except that: in step 1, only titanyl sulfate is doped without dicyandiamide, the material obtained in step 2 is named TiOS, and finally step 3 is to obtain a lithium aluminum hydride-doped hydrogen storage material with a doping amount of 7 wt% of the titanyl sulfate calcined product, which is named LiAlH4-TiOS.
[0070] The XRD test results of TiOS are as follows Figure 1As shown, TiOS contains the characteristic peak of titanyl sulfate, and not only does it lack the characteristic peak of g-C3N4, but it also lacks the characteristic peak of TiO2. The test results show that without doping with dicyandiamide as a carbon source and a nitrogen source, g-C3N4 cannot be generated. However, during the calcination process of titanyl sulfate, TiO2 cannot be obtained. Instead, some titanyl sulfate loses its crystal water. Combined with the existing literature [D.Sofronov, M.Rucki, O.Demidov, et al.Formation ofTiO2 particles during thermal decomposition of Ti(NO3)4, TiOF2 and TiOSO4, Journal of Materials Research and Technology 9 (2020) 12201-12212.], it can be seen that pure titanyl sulfate without any doping will not decompose into TiO2 at 700°C. Therefore, in step 2 of the present invention, under the condition that the calcination temperature is only 520°C, doping titanyl sulfate alone cannot decompose to obtain TiO2, that is, doping with dicyandiamide can enable titanyl sulfate to be prepared by calcination to obtain TiO2.
[0071] The test results of the programmed temperature dehydrogenation experiment of LiAlH4-TiOS are as follows Figure 7 As shown, the initial dehydrogenation temperature is 118°C, the dehydrogenation amount is 6.8wt%, and the dehydrogenation rate is 69.6%. Compared with the test results of Example 1, it can be seen that the addition of dicyandiamide and titanyl sulfate can slightly increase the dehydrogenation amount, but the effect on the initial dehydrogenation temperature is significant, which reduces the initial dehydrogenation temperature from 118°C to 76°C, which proves that dicyandiamide can improve the dehydrogenation performance of LiAlH4.
[0072] The following conclusions can be drawn from Example 1, Comparative Example 2 and Comparative Example 3:
[0073] 1. The role of dicyandiamide is not only as a carbon source and nitrogen source, directly affecting the preparation of g-C3N4, but also has the technical effect of catalyzing the decomposition of titanyl sulfate to prepare TiO2;
[0074] 2. The role of titanyl sulfate is to serve as a titanium source, and the technical effect of obtaining TiO2 by calcining under the conditions of dicyandiamide.
[0075] Comparative Example 4
[0076] A method for preparing lithium aluminum hydride without any doping catalyst, wherein the steps not specifically described are the same as those in Example 1, except that: step 3 is not doped, and finally step 3 can obtain lithium aluminum hydride, named LiAlH4.
[0077] The test results of LiAlH4 temperature-programmed dehydrogenation experiment are as follows Figure 7 As shown, the initial dehydrogenation temperature is 128°C, the dehydrogenation amount is 7.3wt%, and the dehydrogenation rate is 69.5%.
[0078] Compared with the test results of Example 1, it can be seen that the simultaneous addition of dicyandiamide and titanyl sulfate slightly increases the hydrogen desorption rate from 69.5% to 70.6%. However, the effect of the initial hydrogen desorption temperature is particularly significant, which reduces the initial hydrogen desorption temperature from 128°C to 76°C, which proves that the simultaneous addition of dicyandiamide and titanyl sulfate can improve the hydrogen desorption performance of LiAlH4.
[0079] Compared with the test results of Comparative Example 2, it can be seen that the addition of dicyandiamide alone to form g-C3N4 not only reduces the hydrogen decomposition rate from 69.5% to 68.6%, but also can only reduce the initial hydrogen decomposition temperature from 128°C to 119°C, which proves that the addition of dicyandiamide alone has almost no effect on improving the hydrogen decomposition performance of LiAlH4.
[0080] Compared with the test results of Comparative Example 3, it can be seen that the addition of titanyl sulfate alone has a similar effect to the addition of dicyandiamide alone to form g-C3N4, and also reduces the hydrogen decomposition rate from 69.5% to 68.6%. Moreover, it can only reduce the initial hydrogen decomposition temperature from 128°C to 123°C, which proves that the addition of titanyl sulfate alone has almost no effect on improving the hydrogen decomposition performance of LiAlH4.
[0081] By comparing Example 1 with Comparative Examples 2, 3 and 4, the following conclusion can be drawn: adding dicyandiamide or titanyl sulfate alone cannot effectively improve the initial hydrogen decomposition temperature and the hydrogen decomposition rate, and only by adding dicyandiamide and titanyl sulfate at the same time can the technical effect of significantly reducing the initial hydrogen decomposition temperature be obtained, which proves that dicyandiamide and titanyl sulfate have a uniform synergistic effect.
[0082] The isothermal hydrogen desorption test results of LiAlH4 are as follows Figure 5 As shown, the amount of hydrogen released by LiAlH4 at 90°C for 60 minutes is 0.3wt%, and the rate of hydrogen release is 2.8%. Compared with the test results of Example 1, it can be seen that at 90°C for 60 minutes, adding dicyandiamide and titanyl sulfate simultaneously can effectively increase the amount of hydrogen released and the rate of hydrogen release, which proves that the hydrogen release kinetics of LiAlH4 can be effectively improved, especially the hydrogen release kinetics under low temperature conditions.
[0083] In order to further demonstrate the effect of the preparation method of the present invention on the performance, comparative example 5 is provided, in which commercially purchased TiO2-E is used as the titanium source. At the same time, in order to achieve the control variable and eliminate the influence of g-C3N4, an equal amount of g-C3N4 obtained in comparative example 2 is doped to prepare a lithium hydride aluminum-based hydrogen storage material.
[0084] In addition, in order to obtain more comparative conclusions, Comparative Example 6 is provided as a reference example. Wherein, Comparative Example 6 is a lithium hydride aluminum-based hydrogen storage material doped with TiO2-E as a titanium source and not doped with dicyandiamide or g-C3N4.
[0085] Comparative Example 5
[0086] A method for preparing a lithium aluminum hydride-based hydrogen storage material using TiO2-E as a titanium source, wherein the steps not specifically described are the same as those in Example 1, except that: in step 3, TiO2-E and g-C3N4 are used instead of TiO2@g-C3N4, the doping amount of TiO2-E is 0.0105g, and the doping amount of g-C3N4 is 0.0105g. Finally, step 3 can obtain a graphite phase carbon nitride mixed with titanium dioxide doped lithium aluminum hydride hydrogen storage material with a doping amount of 7wt%, which is named LiAlH4-TiO2-Eg-C3N4.
[0087] The test results of the programmed temperature dehydrogenation experiment of LiAlH4-TiO2-Eg-C3N4 are as follows Figure 8 As shown, the initial dehydrogenation temperature is 104°C, the dehydrogenation amount is 6.9wt%, and the dehydrogenation rate is 70.6%.
[0088] Compared with the test results of Example 1, it can be seen that the TiO2@g-C3N4 prepared by simultaneously adding dicyandiamide and titanyl sulfate has almost no effect on the amount of hydrogen desorption, which proves that different preparation methods have almost no effect on the amount of hydrogen desorption. However, the initial hydrogen desorption temperature can be reduced from 104°C to 76°C, which proves that the preparation method of the present invention and the prepared TiO2@g-C3N4 can significantly reduce the initial hydrogen desorption temperature of LiAlH4.
[0089] Comparative Example 6
[0090] A lithium aluminum hydride-based hydrogen storage material doped only with TiO2-E, wherein the steps not specifically described are the same as those in Comparative Example 5, except that: in step 3, only TiO2-E is doped without adding g-C3N4, and finally step 3 can obtain the purchased titanium dioxide-doped lithium aluminum hydride hydrogen storage material with a doping amount of 7 wt%, which is named LiAlH4-TiO2-E.
[0091] The XRD test results of TiO2-E are as follows Figure 1 As shown, it contains the characteristic peak of TiO2. Compared with the test results of Example 1, the XRD diffraction peak of TiO2 in TiO2@g-C3N4 is shifted to the left by 0.06° compared with the XRD diffraction peak of TiO2-E. This phenomenon shows that there is an interaction between TiO2 and g-C3N4 in the TiO2@g-C3N4 prepared by the preparation method of the present invention.
[0092] The test results of the programmed temperature dehydrogenation experiment of LiAlH4-TiO2-E are as follows Figure 7 As shown, the initial dehydrogenation temperature is 94°C, the dehydrogenation amount is 7.0wt%, and the dehydrogenation rate is 71.7%.
[0093] Compared with the test results of comparative example 5, it can be seen that by directly adding g-C3N4, the initial hydrogen desorption temperature also increased from 94°C to 104°C. This phenomenon can draw the following two conclusions:
[0094] 1. Prove that the preparation method of the present invention and the obtained TiO2@g-C3N4 can significantly improve the hydrogen release performance of LiAlH4;
[0095] 2. It is further proved that in TiO2@g-C3N4, TiO2 and g-C3N4 are not a simple physical mixing relationship, but as shown in the XRD test results, there is an interaction between TiO2 and g-C3N4.
[0096] In order to further demonstrate the role of g-C3N4 in the technical solution, Comparative Example 7 is provided, in which a lithium aluminum hydride-based hydrogen storage material is prepared by using carbon nanotubes CNTs instead of g-C3N4.
[0097] Comparative Example 7
[0098] A method for preparing a lithium aluminum hydride-based hydrogen storage material based on CNTs, wherein the steps not specifically described are the same as those in Comparative Example 5, except that: CNTs are used instead of g-C3N4 in step 3, that is, TiO2-E and CNTs are used instead of TiO2@g-C3N4 in step 3, the doping amount of TiO2-E is 0.0105 g, and the doping amount of CNTs is 0.0105 g. Finally, step 3 can obtain a lithium aluminum hydride hydrogen storage material doped with a mixture of titanium dioxide and carbon nanotubes with a doping amount of 7 wt%, which is named LiAlH4-TiO2-E-CNTs.
[0099] The results of the programmed temperature dehydrogenation experiment of LiAlH4-TiO2-E-CNTs are shown in Figure 8 As shown, the initial dehydrogenation temperature is 124°C, the dehydrogenation amount is 6.9wt%, and the dehydrogenation rate is 70.6%. Compared with the test results of Comparative Example 5, it can be seen that replacing g-C3N4 with CNTs has almost no effect on the dehydrogenation amount, but has a significant effect on the initial dehydrogenation temperature. Adding g-C3N4 reduces the initial dehydrogenation temperature from 124°C to 104°C, which proves that g-C3N4 can significantly reduce the initial dehydrogenation temperature of LiAlH4.
[0100] In order to demonstrate the effect of the doping amount of TiO2@g-C3N4 on the performance, Examples 2 and 3 are provided, namely graphite phase carbon nitride-based titanium dioxide doped lithium aluminum hydride hydrogen storage materials with doping amounts of 3wt% and 10wt%, respectively.
[0101] Example 2
[0102] A method for preparing a graphite-phase carbon nitride-based titanium dioxide doped lithium aluminum hydride hydrogen storage material, wherein the steps not specifically described are the same as those in Example 1, except that: in the step 3, the doping amount of TiO2@g-C3N4 is 3wt%, i.e., 0.009g TiO2@g-C3N4 and 0.291g LiAlH4, and finally step 3 can obtain a graphite-phase carbon nitride-based titanium dioxide doped lithium aluminum hydride hydrogen storage material with a doping amount of 3wt%, named LiAlH4 / TiO2@g-C3N4-3.
[0103] The results of the programmed temperature dehydrogenation experiment of LiAlH4 / TiO2@g-C3N4-3 are shown in Figure 5 As shown, the initial dehydrogenation temperature is 82.3°C, the dehydrogenation amount is 7.3wt%, and the dehydrogenation rate is 71.7%.
[0104] Example 3
[0105] A method for preparing a graphite-phase carbon nitride-based titanium dioxide doped lithium aluminum hydride hydrogen storage material, wherein the steps not specifically described are the same as those in Example 1, except that: in the step 3, the doping amount of TiO2@g-C3N4 is 10wt%, i.e., 0.030g TiO2@g-C3N4 and 0.270g LiAlH4, and finally step 3 can obtain a graphite-phase carbon nitride-based titanium dioxide doped lithium aluminum hydride hydrogen storage material with a doping amount of 10wt%, named LiAlH4 / TiO2@g-C3N4-10.
[0106] The results of the programmed temperature dehydrogenation experiment of LiAlH4 / TiO2@g-C3N4-10 are shown in Figure 5 As shown, the initial dehydrogenation temperature is 72°C, the dehydrogenation amount is 6.6wt%, and the dehydrogenation rate is 69.8%.
[0107] By comparing Example 1 with Example 2 and Example 3, the following conclusion can be drawn: as the doping amount of TiO2@g-C3N4 increases, although the hydrogen decomposition amount of LiAlH4 / TiO2@g-C3N4 will decrease slightly, the initial hydrogen decomposition temperature will decrease significantly.
Claims
1. A graphite phase carbon nitride-based titanium dioxide doped lithium aluminum hydride hydrogen storage material, characterized in that: Dicyandiamide and titanyl sulfate are used as raw materials, dicyandiamide is used as a carbon source and a nitrogen source, and titanyl sulfate is used as a titanium source; after grinding and mixing, they are calcined to obtain TiO2@g-C3N4, and then ball-milled with lithium aluminum hydride to obtain a graphite phase carbon nitride-based titanium dioxide doped with lithium aluminum hydride hydrogen storage material; The doping amount of the TiO2@g-C3N4 is 3-10wt%; The microstructure of the g-C3N4 is a porous structure, the microstructure of TiO2 is a nanoparticle structure, the particle size of the TiO2 nanoparticles is 8-9nm, and the microstructure of TiO2@g-C3N4 is that TiO2 is uniformly loaded on the surface of g-C3N4.
2. A method for preparing a graphite phase carbon nitride-based titanium dioxide doped lithium aluminum hydride hydrogen storage material, characterized in that The following steps are involved: Step 1, pretreatment of raw materials, grinding dicyandiamide and titanyl sulfate under certain conditions and in a certain mass ratio to obtain a mixture TC-F; Step 2, preparation of graphite phase carbon nitride-based titanium dioxide, calcining the TC-F obtained in step 1 under certain conditions; finally, grinding the calcined product under certain conditions, and drying under certain conditions to obtain graphite phase carbon nitride-based titanium dioxide, named TiO2@g-C3N4; Step 3, preparation of graphite phase carbon nitride-based titanium dioxide doped lithium aluminum hydride hydrogen storage material, using the TiO2@g-C3N4 obtained in step 1 as a catalyst, with a certain doping amount, TiO2@g-C3N4 and LiAlH4 are ball-milled under certain conditions to obtain graphite phase carbon nitride-based titanium dioxide doped lithium aluminum hydride hydrogen storage material, named LiAlH4 / TiO2@g-C3N4.
3. The preparation method according to claim 2, characterized in that: In the step 1, the grinding condition is infrared irradiation, and the grinding time is 0.5-1h; the mass ratio of dicyandiamide to titanyl sulfate is (1-3):
1.
4. The preparation method according to claim 2, characterized in that: In the step 2, the calcination conditions are: under air conditions, the heating rate is 3-10°C / min, the calcination temperature is 440-550°C, and the calcination time is 2-4h; the grinding time is 0.5-1h; the drying conditions are: the drying temperature is 60-80°C, and the drying time is 6-12h.
5. The preparation method according to claim 2, characterized in that: In the step 3, the doping amount of TiO2@g-C3N4 is 3-10wt%; the ball milling conditions are: under argon conditions, the ball-to-material ratio is (100-200):1, the ball milling speed is 250-500rpm, and the ball milling time is 0.5-1h.
6. Application of a graphite phase carbon nitride-based titanium dioxide doped lithium aluminum hydride hydrogen storage material as a hydrogen storage material, characterized in that: The initial dehydrogenation temperature is 72-82.3°C, the dehydrogenation amount is 6.6-7.3wt%, and the dehydrogenation rate is 69.8-71.7%.